Good Governance of School Administrators Operating under Samut Songkhram Primary Educational Service Area (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aimed to: (1) investigate the level of school administrators’ governance based on the principles of good governance in schools under the Office of the Primary Education Service Area, Samut Songkhram, and (2) compare the governance practices based on gender, educational level, age, and school size. The sample consisted of 375 teachers from schools under the Samut Songkhram Primary Educational Service Area Office for the academic year 2024. The sample size was determined using Krejcie and Morgan’s table, followed by proportional stratified random sampling based on school size and simple random sampling. The research instrument was a 5-point Likert scale questionnaire with an overall reliability coefficient of 0.98. Data were analyzed using frequency, percentage, mean, standard deviation, t-test, and one-way ANOVA. The findings revealed that: (1) among the governance principles practiced by school administrators in schools under the Office of the Primary Education Service Area, Samut Songkhram, overall, the teachers’ opinions on the governance practices of school administrators were at the highest level, and (2) the comparison of governance practices in schools under the Office of the Primary Education Service Area, Samut Songkhram, based on age, and school size revealed statistically significant differences at the 0.05 level.